Vytváření atraktivních investičních podmínek pro zahraniční investory na základě zdokonalování měnové politiky (problém Uzbekistánu) - Amonov, Kholnazar; Tuček, Miroslav, 1929-2017; Janáček, Kamil, 1943-2023; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2008)
Abstract Attracting foreign investments to the economy in a large scale pursues long-term strategic goals for creating civilized, socially-oriented society in Uzbekistan, which is characterized by a high standard of living based on mixed economy. For stabilizing the economy and for improving the investments climate, it is necessary to take a number of arrangements, which will target on forming general terms of development of civilized market relations as well as on special conditions relating directly to problem solving -- how to attract the foreign investments. When analyzing the investment process in Uzbekistan, it is possible to say that the extent of attracting and efficiency of using the foreign investments on the national level as well on the regional levels very often depends upon the abilities to establish relevant legal and economic conditions within each phase of the development of the society. It is essential for Uzbekistan to try to attract foreign investments, which would help and support the development of the domestic industry and contribute to implementation of advanced technologies. Therefore volume of business exchange between the enterprises with foreign investments and Uzbek enterprises serves as a criterion for evaluation of successful attraction of foreign investments. We assume that positives brought by the involvement of foreign enterprises in the Uzbek market, must lie predominantly in using technologies for processing raw materials, which Uzbekistan is very rich in. Policy of monetary exchange rates is an important part of the reform programs realized in transformed economy of Uzbekistan. This policy is crucial for improvement of relative prices, restoration of price stability and for opening national markets to international business -- markets, which were closed so far. Nonexistent convertibility of domestic currency is a reason for decreasing the volume of investments within the country.
It is therefore necessary to introduce liberalization of the monetary market and open a seamless access of the businesses to hard currencies. Issues of investment image of Uzbekistan are closely related to the problem of openness of the national economy, which under the current conditions become extremely meaningful.
Vedoucí práce: Miroslav Tuček
Disertační práce ()—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2008
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2008
Způsob přístupu: Internet
Keywords: finance [obor disert. práce]; disertace; dissertations